Contribution of the Cach Waqf to Achieving Sustainable Development International Experiences - مشري فريد; دوفي قرمية (Finance and Business Economies Review, 2021)
Through this research, we aim to clarify the role of Cach Waqf in achieving sustainable development, the economic, social and environmental dimensions, to revive the developmental role of the endowment as an Islamic financing institution. The study has come to Cach waqf have a role in achieving sustainable development in its economic, social and environmental dimension through establishing and financing investment projects, reducing unemployment, providing a good healthy environment, protecting the environment and introducing the concept of green development